Sustainability of TNF-blocker tapering in rheumatoid arthritis over 3 years: long-term follow-up of the STRASS (Spacing of TNF-blocker injections in Rheumatoid ArthritiS Study) randomised controlled trial. Issue 2 (12th September 2017) - Sigaux, Johanna; Bailly, Florian; Hajage, David; Mariette, Xavier; Morel, Jacques; Gandjbakhch, Frédérique; Foltz, Violaine; Gossec, Laure; Tubach, Florence; Fautrel, Bruno
Abstract : Introduction: We have limited data on the sustainability of tumour necrosis factor (TNF)-blocker tapering in rheumatoid arthritis (RA) in remission over the long term in real-life settings. This study aimed to assess the probability of sustained dose reduction of TNF-blockers in an observational 3-year extended follow-up of the Spacing of TNF-blocker injections in Rheumatoid ArthritiS Study (STRASS), a randomised controlled trial comparing progressive TNF-blocker injections (spacing arm (S-arm) to maintenance arm (M-arm)) in patients with RA in stable remission. Methods: In 2015, clinical data for the completer population were retrospectively collected at 1, 2 and 3 years after the end of the trial. The endpoints were the proportion of patients free of a biological disease-modifying antirheumatic drug (bDMARD) treatment, a sustainably spaced injection of TNF-blockers and a full-dose regimen as well as the mean dose of bDMARD intake and treatment switch rate. Results: Overall, 96 patients (76.8% of the completers) had data available up to 3 years; 11.5% discontinued TNF-blockers (5.8% vs 18.2% in the M-arm and S-arm, p=0.06), 30.2% had a tapered regimen (28.8% vs 31.8%, p=0.76) and 37.5% retained a full dose (44.2% vs 29.5%, p=0.14). The mean TNF-blocker dose quotient was 66% of the full dose (74% vs 58% in the M-arm and S-arm, p=0.06); 20.8% switched to another bDMARD (21.2% vs 20.5%, p=0.94). Conclusion: Sustained TNF-blocker de-escalation or withdrawal is achievable in 41% of patients over 3 years with limited dose reduction. Optimal strategies remain to be determined to maintain remission after TNF-blocker tapering or discontinuation.